Metabolome and Transcriptome Analyses Revealing the Molecular Mechanisms of Precarious Fertility in Quinoa Cultivars - Chao Song; Qingyun Huang; Chunsong Lin; Huihua Li; Ziyang Li; Yiding Xu; Fei Chen; Xueqin Zhang; Zhiqiang Wu; Suxia Xu (Agronomy, 2025)
Quinoa (Chenopodium quinoa Willd) is a tetraploid crop that has provided vital subsistence, nutrition, and medicine for Andean indigenous cultures. In recent years, quinoa has gained global importance all over the world. However, variations in fertility have been frequently observed during the flower development of quinoa, severely affecting quinoa production. To comprehend the fundamental causes of fertility variation in quinoa, this research examined hormonal metabolism and gene expression across three ecotypes: normal fertility (F), absent stamens (S1), and abnormal stamens (S3). S1 and S3 presented absent and abnormal stamens, respectively, compared with F. Phytohormone profiling yielded 60 metabolites and revealed the clear separation between different ecotypes at different developmental stages according to principal component analysis (PCA). The results of transcriptomics showed more DEGs (differentially expressed genes) identified between F and S1 ecotypes (8002 and 10,716 for earlier and later stages, respectively) than F vs. S3 (4500 and 9882 for earlier and later stages, respectively) and S1 vs. S3 (4203 and 5052 for earlier and later stages, respectively). Zeatin biosynthesis and hormone signal transduction pathways were enriched among 19 KEGG (Kyoto Encyclopedia of Genes and Genomes) terms, indicating their potential roles in quinoa flower fertility regulation. The correlation-based network presented the associations between selected hormones and genes, possibly regulating fertile ecotypes. Furthermore, we explored the expression of flower development-related genes in three ecotypes using RT-PCR, showing the higher expressions of AP1, AP3, and FLS in sterile ecotypes than fertile ecotypes at both stages. These findings reveal new insights into the hormonal and genetic regulations of floral fertility in quinoa, which may have consequences for developing high-yielding cultivars.